Analysis of the academic programs offered by public and private universities in Costa Rica for the Preschool career and its relationship with teacher training between the years 2020 and 2021 - Calvo-Achoy, Mayte (2023)
This article presents the results of the research developed by the Pedagogy Chair of the Distance State University (UNED) between 2020 and 2021, which aims to analyze the curriculum offered by both public and private universities in the country for the training of Early Childhood Education professionals. Initially, the article proposes a brief description of the historical milestones that have left their mark on Early Childhood Education and then offers a theoretical reflection on the teacher profile and the importance of this training in the comprehensive care of children. Methodologically, the research is framed in a qualitative approach, incorporating the analysis of information. Objectives and criteria are established to carry out a process of reviewing information that ultimately provides inputs for its interpretation and analysis. The results show similarities and differences in the curriculum offered, as well as the content that should be considered for comprehensive care of the population in early childhood and that are not present in the programs. As a conclusion, the need to carry out improvement actions in the curricular, administrative, and entry areas to the careers is evidenced, as well as improving coordination between different public and private entities that allow for quality training of Early Childhood Education professionals. It is hoped that the results and conclusions of this research will serve as a basis for other studies and will be considered in the design, redesign, and accreditation exercises of Early Childhood Education careers in the country.